The Effect of Fermentation Time on Phenolic Levels of Vanilla (Vanilla planifolia) Leaf Kombucha Tea - Frika Nafisah, Raihana; Shofiyya, Ainina Neihayatus; Agustina, Eva; Lusiana, Nova; Purnamasari, Risa (International Conference on Sustainable Health Promotion, 2023)
Phenolics are compounds that have hydroxyl groups and can be found in plant parts, such as vanilla leaves. Vanilla leaves can be used as a base for making kombucha tea. The length of time of fermentation can affect the resulting kombucha tea products. The purpose of this study was to determine the effect of fermentation time on the phenolic content of vanilla leaf kombucha tea. This study used experimental research which included titrated total acid level test, pH level test and phenolic content test with variations of 0, 4, 8 and 12 days. The results showed that the phenolic content of kombucha vanilla leaf tea on day 0 was 37.995 ppm; 42.188 ppm on the 4th day; 57.58 ppm on the 8th day; and 50.53 ppm on the 12th day. Therefore, the highest phenolic concentration was found on the 8th day.